Surveillance of antimicrobial susceptibilities reveals high proportions of multidrug resistance in toxigenic Clostridium difficile strains in different areas of Poland. (April 2020) - Lachowicz, D.; Pituch, H.; Wultańska, D.; Kuijper, E.; Obuch-Woszczatyński, P.
Abstract: Two hundred and fifty-three non-duplicate toxigenic Clostridium difficile isolates, collected from February 2012 to December 2014, were evaluated for phenotypic resistance to ten antimicrobial drugs with the E-test gradient diffusion method. All strains of C. difficile were susceptible to metronidazole, vancomycin, and tigecycline. The metronidazole MIC values of the hyperepidemic PCR-ribotypes RT027 and RT176 were higher than those of non-epidemic PCR-ribotypes (p < 0.05, as evidenced by Mann-Whitney U test). In contrast, vancomycin susceptibility did not differ between hyperepidemic and non-epidemic strains, although the difference was almost significant (p = 0.065). Clostridium difficile RT027 and RT176 isolates could be assessed to five and four different susceptibility patterns, respectively, representing various combinations of resistance to different antimicrobial classes. A single point mutation (Thr82Ile) in the gyrA gene was detected in 11 (78.6%) of 14 isolates with high level of resistance to ciprofloxacin and moxifloxacin and four different types of single point mutations (Arg447Lys, Ser416Ala, Asp426Val, Asp426Asn) in the gyrB gene were detected in 4 strains, also with high level of resistance to ciprofloxacin and moxifloxacin. Four different point mutations were detected in the rpoB gene in 21 rifampicin-resistant strains of which one has not been reported previously, Gln489Leu. This study demonstrates the presence of multidrug-resistant C. difficile strains in Polish hospitals over the study period, irrespective of geographical location or reference level of the hospital. Highlights: We demonstrates highly diversified susceptibility patterns of Polish C. difficile . We clarified that MDR C. difficile strains dominated in hospital setting. Higher percentage of RI resistant strains was observed.